2005
DOI: 10.1021/ol050910r
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Highly Enantioselective Synthesis of β-Alkynyl-β-amino Esters through Ag-Catalyzed Asymmetric Mannich Reactions of Silylketene Acetals and Alkynyl Imines

Abstract: [reaction: see text] A readily available iso-leucine-based phosphine ligand is used to promote Ag-catalyzed Mannich reactions between silylketene acetals and various alkynyl imines. Reactions can be effected in the presence of 5 mol % catalyst, without the need for rigorous exclusion of air, and with commercially available solvents (without purification) to afford the desired beta-alkynyl-beta-amino esters in 84-94% ee and 61-91% isolated yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…In this study the compounds 7 or 8 or 9 were synthesized (Fig. 3) by the reaction of 3 or 5 or 6 with ethylenediamine using boric acid as catalyst, because it is not an expensive reagent and no special conditions are required for use 36 . H NMR spectrum for 9 at; 0.07 and 0.90 ppm for ter-butyldimethylsylane fragment; at 1.50, 1.52 and 2.00 ppm for methylene groups of arm bound to cyclobutane ring; at 3.08-3.52 and 3.66 ppm for methylene groups involved in the arm bound to A-ring of steroid; at 3.08-3.52 and 3.66 ppm for methylene groups bound to both imino and amino groups; at 4.10 ppm for both hydroxyl and amino groups; at 5.40 ppm for cyclobutane ring.…”
Section: Preparation Of Cyclobutene-ol-steroid-amino Conjugatesmentioning
confidence: 99%
“…In this study the compounds 7 or 8 or 9 were synthesized (Fig. 3) by the reaction of 3 or 5 or 6 with ethylenediamine using boric acid as catalyst, because it is not an expensive reagent and no special conditions are required for use 36 . H NMR spectrum for 9 at; 0.07 and 0.90 ppm for ter-butyldimethylsylane fragment; at 1.50, 1.52 and 2.00 ppm for methylene groups of arm bound to cyclobutane ring; at 3.08-3.52 and 3.66 ppm for methylene groups involved in the arm bound to A-ring of steroid; at 3.08-3.52 and 3.66 ppm for methylene groups bound to both imino and amino groups; at 4.10 ppm for both hydroxyl and amino groups; at 5.40 ppm for cyclobutane ring.…”
Section: Preparation Of Cyclobutene-ol-steroid-amino Conjugatesmentioning
confidence: 99%
“…7d, 37 In related reactions, Snapper and Hoveyda et al reported an asymmetric version of Mannich-type reactions catalyzed by silver acetate. 38,39 Propargyl imines proved to be susceptible to nucleophilic addition of silylenol ethers derived from acetate esters in the presence of silver acetate and a ligand derived from an amino acid (Table 10.3). In this reaction,chiralb-aminoesterswere obtainedin highyieldandgoodenantioselectivity.…”
Section: Silver As a Lewis Acid Reagentmentioning
confidence: 99%
“…Furthermore, this method is applicable to a combination of silyl keteneacetals and alkynylimines (Scheme 9.17). 27 In 2006, Hoveyda and coworkers developed an asymmetric Mannich reaction of silyloxyfurans and aldimines using a similar catalyst system (Scheme 9.18). 28 The diastereo-and enantioselective reaction between silyloxyfurans and aldimines in the presence of catalyst gave g-butenolides, which are useful building blocks for organic synthesis.…”
Section: Mannich Reactionmentioning
confidence: 99%